Surface-modified ammonia decomposition catalyst and preparation method thereof

By supporting the active metal on the porous carbon material support and depositing a protective layer of silica, the problem of easy decomposition and agglomeration of ammonia decomposition catalysts at high temperatures is solved, the anti-sintering and dispersion properties of the catalysts are improved, and the efficient ammonia decomposition catalysts are achieved preparation.

CN119140178AInactive Publication Date: 2024-12-17INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411606838.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing ammonia decomposition catalysts are prone to decomposition and reactive metal agglomeration at high temperatures, resulting in a decrease in catalytic stability and dispersion, making it difficult to achieve industrial application.

Method used

Plasma enhanced chemical vapor deposition method is used to support active metals on the porous carbon material support, and oxide protective layers such as silica are deposited to form a core-shell structure to improve the anti-sintering and dispersion properties of the catalyst.

Benefits of technology

Effectively prevent the agglomeration of active metals, improve the anti-sintering performance and dispersion of the catalyst, simplify the preparation process, reduce costs, and realize the industrial application of highly efficient ammonia decomposition catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140178A_ABST
    Figure CN119140178A_ABST
Patent Text Reader

Abstract

The invention discloses a surface-modified ammonia decomposition catalyst and a preparation method thereof, and belongs to the technical field of ammonia decomposition catalysts.The surface-modified ammonia decomposition catalyst is prepared by taking a porous carbon material as a carrier, loading one or more than two active metals of Ru, Ni, Fe, Co and the like through dipping and chemical vapor deposition methods, and then preparing the surface-modified ammonia decomposition catalyst. And depositing oxides such as silicon dioxide, aluminum oxide and zirconium oxide on the surface through a plasma vapor deposition method to realize surface modification of the catalyst. On one hand, the surface modification can overcome the defects that a porous carbon material as a carrier is easy to react with ammonia at high temperature and is unstable, and fully exerts the advantages of high specific surface area, excellent electric conductivity, excellent thermal conductivity and the like; on the other hand, the silicon dioxide layer wraps the surface of the catalyst to form a similar core-shell structure, so that the active metal can be effectively fixed on the surface of the carrier, the agglomeration of active metal particles is reduced, and the anti-sintering capability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ammonia decomposition catalysts, and in particular relates to a surface-modified ammonia decomposition catalyst and a preparation method thereof. Background Art

[0002] The development of a sustainable society depends on the efficient storage, transportation and use of renewable energy. Hydrogen has attracted much attention as a clean and efficient energy source, among which sustainable hydrogen production through water electrolysis and biomass conversion has made great progress. However, due to the low volume energy density of hydrogen, high storage and transportation costs; and flammability and explosion, poor safety, how to achieve safe and efficient storage and transportation of hydrogen remains the key to large-scale application. Ammonia, as an efficient hydrogen storage medium, has the advantages of high energy density, low liquefaction storage and transportation costs, and high safety. It has great prospects for use in large-scale hydrogen storage. In the past decade, people have conducted extensive research on the processes and technologies of ammonia decomposition, with the main goal of producing carbon-free, high-purity hydrogen. In general, there are three main challenges to establishing a future hydrogen economy: synthesizing cheap but efficient catalysts, designing efficient reactors, and developing hydrogen purification technologies. Among them, synthesizing cheap and efficient catalysts is one of the challenges to realizing the future hydrogen economy.

[0003] Commonly used ammonia decomposition catalysts include Ru, Ni, and Fe-based catalysts, among which Ru-based catalysts have the best catalytic performance, but are limited by their high prices, which is not conducive to industrial applications. Non-precious metal catalysts (such as Ni and Fe-based catalysts) are relatively cheap but their catalytic efficiency is not high enough. The decomposition performance of the catalyst can be appropriately improved by increasing the active metal loading. However, when the loading is high, it is easy to cause metal agglomeration, reduced dispersibility, and reduced catalytic stability. By changing the carrier structure and regulating the interaction between metal and carrier, the problems of agglomeration and poor dispersibility of active metals can be improved. Common carriers for ammonia decomposition hydrogen production catalysts include SiO2, Al2O3, MgO, carbon materials (such as activated carbon, carbon nanotubes, carbon nanofibers, graphene), etc. Among them, carbon materials have a large specific surface area and excellent conductivity, and are often used as carriers for studying low-temperature and high-activity catalysts. In addition, the synergistic effect between nanocarbon material carriers and active metals can further promote the catalytic performance of ammonia decomposition. Taking Ru / CNT as an example, on the one hand, the carboxyl and hydroxyl groups on the surface of carbon nanotubes can fix the Ru atoms well; on the other hand, Ru atoms can enter the pores of carbon nanotubes and are constrained. These have a certain effect on reducing atomic aggregation and improving dispersion. However, in high temperature environments, carbon materials are easy to decompose and react with ammonia (when the temperature exceeds 800°C, carbon nanotubes may decompose).

[0004] Research reports show that core-shell catalysts formed by coating active metals such as silicon oxide and zirconium oxide have better sintering resistance and are not easy to agglomerate when working at high temperatures. The main methods for preparing core-shell structures are hydrothermal method and modified Stöber method, which usually have a long reaction time and a complicated preparation process. In addition, polyvinyl pyrrolidone (PVP) is generally added as a template, which has the problem of incomplete removal and easy residue. Summary of the invention

[0005] In view of the technical problems raised by the above technical background, the present invention proposes a method for coating the surface of an ammonia decomposition catalyst by a plasma enhanced chemical vapor deposition method to improve the dispersibility and anti-sintering performance, thereby achieving the purpose of surface enhancement modification. Specifically, a porous carbon material is used as a carrier, and an active metal is first loaded by an impregnation method, and then modified on the catalyst surface by plasma enhanced vapor deposition, and oxides such as silicon dioxide are deposited (plasma can improve the reactivity of inorganic chemical monomers, and a variety of materials including inert materials can be used as precursors) to enhance the strength of the carrier and improve the anti-sintering and dispersibility of the catalyst.

[0006] The technical solution of the present invention is as follows: A method for preparing a surface-modified ammonia decomposition catalyst comprises the following steps: Step 1: Preparation of loaded active metal by impregnation method: Weigh the loaded active metal and dissolve it in deionized water, stir and mix it evenly, use it as the impregnation solution, select the porous material as the carrier, add the carrier into an equal volume of the impregnation solution, continue to ultrasonicate after mixing, then stand at room temperature, and then dry it in an oven overnight to obtain a catalyst precursor loaded with active metals; Step 2: Modification and enhancement of catalyst surface: The catalyst precursor prepared in step 1 is placed in the reaction zone of the quartz tube, the heating temperature is set to 300°C, the chamber is evacuated to a vacuum, and then the reaction gas containing the deposition layer source material is introduced, the RF power supply is turned on to start the plasma, and the heating zone is started to start the reaction. The reaction time is 5-20 minutes. After the reaction is completed, the RF power supply and the heating device are turned off, and nitrogen is continued to be purged in the chamber for 30 minutes to remove the residual reactants on the surface.

[0007] In the above technical solution, in step 1, the loaded active metal is one or two of RuCl3·3H2O, Ni(NO3)3·6H2O, Fe(NO3)3·9H2O, and Co(NO3)2·6H2O.

[0008] In the above technical solution, in step 1, the porous material is a molecular sieve, a metal organic framework material (MOF) or a porous carbon material.

[0009] In the above technical solution, in step 1, the porous carbon material includes but is not limited to carbon nanotube sponge, graphene sponge or carbon foam.

[0010] In the above technical solution, in step 1, the carrier is added to the impregnation solution while being ultrasonically treated, and the ultrasonic process is used instead of the stirring process.

[0011] In the above technical solution, in step 1, the ultrasonic time is 20 minutes, the standing time is 8-12 hours, the temperature of the oven is 100°C, the room temperature is 10°C~30°C, and the overnight time is 8-12 hours.

[0012] In the above technical solution, in step 2, the deposited layer is silicon oxide, aluminum oxide, zirconium oxide, silicon carbide or silicon nitride.

[0013] In the above technical solution, in step 2, the reaction gas carrying the deposition layer source material is oxygen and nitrogen carrying tetraethoxysilane.

[0014] In the above technical solution, in step 2, the tetraethoxysilane is heated in a water bath at 45°C.

[0015] In the above technical solution, in step 2, the temperature of the heating zone is 200-300°C.

[0016] Beneficial effects: The present invention deposits protective layers such as silicon oxide on the surface of the ammonia decomposition catalyst by a plasma enhanced chemical vapor deposition method. On the one hand, it can overcome the drawbacks of porous carbon materials as carriers, which are easy to react with ammonia at high temperatures and unstable, and give full play to its advantages such as high specific surface area, excellent electrical conductivity and thermal conductivity; on the other hand, the silicon dioxide layer is wrapped on the catalyst surface to form a similar core-shell structure, which can effectively fix the active metal on the carrier surface, prevent agglomeration, and improve the anti-sintering ability. In addition, the method is simple and easy to operate, and can realize the efficient preparation of ammonia decomposition catalysts. In addition, porous carbon materials with different shapes and pore sizes can be directly selected as carriers as needed, and their pore size and shape are fixed, eliminating the step of granulation molding required after conventional catalyst preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic diagram of a device for surface modification of an ammonia decomposition catalyst; Figure 2 This is a partial enlarged view of the catalyst surface modification process. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0019] Example 1 Equipment used in a method for preparing a surface-modified ammonia decomposition catalyst like Figure 1 As shown, the gases used are nitrogen and oxygen, wherein oxygen as a reaction gas can be directly supplied to the plasma enhanced chemical vapor phase equipment; nitrogen as a carrier gas needs to pass through tetraethoxysilane (TEOS) heated by a constant temperature water bath before being connected to the plasma enhanced chemical vapor phase equipment.

[0020] like Figure 2 As shown, the front end area is the plasma working area, where the gas source material required for growth is subjected to the action of plasma, the molecules are activated and react; then, it is transported to the rear end heating area by the carrier gas, and a silicon oxide layer is deposited and coated on the surface of the catalyst precursor.

[0021] Example 2 A method for preparing a surface-modified ammonia decomposition catalyst comprises the following steps: 1) Loading active metals by impregnation method According to the different proportions of active metals to be loaded (such as mass fractions of 10%, 15%, 20%, 30%, and 40%), weigh a certain amount of one or two of RuCl3·3H2O, Ni(NO3)3·6H2O, Fe(NO3)3·9H2O, and Co(NO3)2·6H2O (loading two or more different active metals is called bimetallic or multimetallic catalysts), dissolve in deionized water, and stir and mix evenly as the impregnation solution. Select porous carbon materials as carriers, including but not limited to carbon nanotube sponges, graphene sponges, and carbon foams, add the carriers to an equal volume of the impregnation solution, and add while ultrasonic treatment (using ultrasonic process instead of stirring). After mixing, continue ultrasonication for 20 minutes, and then stand at room temperature for 8-12 hours. Then dry in an oven at 100 ° C overnight to obtain a catalyst precursor loaded with active metals.

[0022] 2) Modification and enhancement of catalyst surface A nanometer-thick silicon dioxide layer is deposited on the surface of the pre-catalyst as a protective layer by plasma enhanced chemical vapor deposition (PECVD). The pre-prepared catalyst is placed in the reaction zone of the quartz tube and the heating temperature is set to 300°C. The PECVD chamber is evacuated to a vacuum, and then oxygen and nitrogen containing tetraethoxysilane (TEOS) (nitrogen is tetraethoxysilane heated in a 45°C water bath) are introduced. TEOS, as a silicon source, can react with oxygen to form silicon dioxide, which is deposited on the catalyst surface. Turn on the RF power supply to start the plasma, and start the heating zone (temperature at 200-300°C) to start the reaction. The reaction time is 5-20 minutes. The longer the reaction time, the thicker the deposited silicon dioxide layer. After the reaction is completed, turn off the RF power supply and the heating device, and continue to purge nitrogen in the chamber for 30 minutes to remove the residual reactants on the surface.

[0023] The deposited protective layer can be silicon oxide, aluminum oxide, zirconium oxide, silicon carbide, silicon nitride, etc., and different source materials can be selected according to the deposited layer; porous carbon materials are selected as carriers, including but not limited to carbon nanotube sponges, graphene sponges, carbon foams, etc., and can be extended to other porous materials, such as molecular sieves, MOFs and other porous materials.

[0024] 3) Characterization of ammonia decomposition catalyst performance A certain mass of ammonia decomposition catalyst was loaded into a fixed bed reactor, and the ammonia decomposition rate was tested at 500°C, 550°C, 600°C, 650°C, and 700°C, respectively, with a flow rate of 83.5 ml / min and a space velocity of 10020 ml / g / h. The ammonia conversion rate can be calculated by the formula: Ammonia conversion rate = (initial ammonia content - tail gas ammonia content) / initial ammonia content × 100%.

[0025] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a surface-modified ammonia decomposition catalyst, characterized in that: The steps include: Step 1: Preparation of loaded active metal by impregnation method: Weigh the loaded active metal and dissolve it in deionized water, stir and mix it evenly, use it as the impregnation solution, select the porous material as the carrier, add the carrier into an equal volume of the impregnation solution, continue to ultrasonicate after mixing, then stand at room temperature, and then dry it in an oven overnight to obtain a catalyst precursor loaded with active metals; Step 2: Modification and enhancement of catalyst surface: The catalyst precursor prepared in step 1 is placed in the reaction zone of the quartz tube, the heating temperature is set to 300°C, the chamber is evacuated to a vacuum, and then the reaction gas containing the deposition layer source material is introduced, the RF power supply is turned on to start the plasma, and the heating zone is started to start the reaction. The reaction time is 5-20 minutes. After the reaction is completed, the RF power supply and the heating device are turned off, and nitrogen is continued to be purged in the chamber for 30 minutes to remove the residual reactants on the surface.

2. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 1, characterized in that: In step 1, the loaded active metal is one or two of RuCl3·3H2O, Ni(NO3)3·6H2O, Fe(NO3)3·9H2O, and Co(NO3)2·6H2O.

3. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 1, characterized in that: In step 1, the porous material is a molecular sieve, a metal organic framework material or a porous carbon material.

4. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 3, characterized in that: In step 1, the porous carbon material is carbon nanotube sponge, graphene sponge or carbon foam.

5. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 1, characterized in that: In step 1, the carrier is added to the impregnation solution while being subjected to ultrasonic treatment.

6. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 1, characterized in that: In step 1, the ultrasonication time is 20 minutes, the standing time is 8-12 hours, the oven temperature is 100° C., the room temperature is 10° C.-30° C., and the overnight time is 8-12 hours.

7. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 1, characterized in that: In step 2, the deposited layer is silicon oxide, aluminum oxide, zirconium oxide, silicon carbide or silicon nitride.

8. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 1, characterized in that: In step 2, the reaction gas carrying the deposition layer source material is oxygen and nitrogen carrying tetraethoxysilane.

9. The method for preparing a surface-modified ammonia decomposition catalyst according to claim 1, characterized in that: In step 2, the temperature of the heating zone is 200-300°C.

10. A catalyst prepared by the method for preparing a surface-modified ammonia decomposition catalyst according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-brightness PSS composite substrate and manufacturing method thereof

    CN110429160A

  • Preparation method and application of modified monolithic catalyst for hydrogen production through ammonia decomposition

    CN118384877A